2015
DOI: 10.5195/emaj.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corporate Performance and Ownership Structure: Evidence from Turkey

Abstract: This study investigates the effects of ownership structure on the performance of the listed companies in Borsa Istanbul Stock Exchange 30 Firms (BIST 30). The main hypothesis of our study is that there is a significant relationship between companies' performances and their ownership structures.The statistical population includes 19 non-financial companies in the period of years between 2008 and 2013. The results show that the concentration of the large shares of companies one or a few share holders has a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…The existing literature also found an inverse relation between operating leverage and profitability, which is also concluded by Baker (1973) and Selling and Stickney (1989). We also found two control variables, that is, promoters holding and firm size, which have a negative relationship with MVA (Athanasoglou et al, 2008;Ersoy & Koy, 2015;Lehmann & Weigand, 2000;Thonet & Poensgen, 1979;Qi & Wu, 2006).…”
Section: Relationship Between Market Value Added and Degree Of Operat...supporting
confidence: 76%
See 1 more Smart Citation
“…The existing literature also found an inverse relation between operating leverage and profitability, which is also concluded by Baker (1973) and Selling and Stickney (1989). We also found two control variables, that is, promoters holding and firm size, which have a negative relationship with MVA (Athanasoglou et al, 2008;Ersoy & Koy, 2015;Lehmann & Weigand, 2000;Thonet & Poensgen, 1979;Qi & Wu, 2006).…”
Section: Relationship Between Market Value Added and Degree Of Operat...supporting
confidence: 76%
“…The prime reason for this interference by promoters is to secure their claim over present cashflows. Previous literature found the same relationship (Ersoy & Koy, 2015; Lehmann & Weigand, 2000; Thonet & Poensgen, 1979).…”
Section: Empirical Findingssupporting
confidence: 70%
“…Michael and Eric (2008) discovered that freestanding family owned businesses organizations with a single share class have equivalent market performance than other businesses organizations based on Tobin's q ratios, excellent accounting performance based on ROA. Ersoy (2015) found that the concentration of the large shares of companies one or a few shareholders has a negative effect on related firm's performance. They further demonstrated that large shareholders and concentrated ownership of the firms would actually lead to different financial performances.…”
Section: Wwwccsenetorg/ijefmentioning
confidence: 99%